Clinical features and management of cytomegalovirus corneal endotheliitis: analysis of 106 cases from the Japan corneal endotheliitis study. Issue 1 (29th July 2014) - Koizumi, Noriko; Inatomi, Tsutomu; Suzuki, Takashi; Shiraishi, Atsushi; Ohashi, Yuichi; Kandori, Michiko; Miyazaki, Dai; Inoue, Yoshitsugu; Soma, Takeshi; Nishida, Kohji; Takase, Hiroshi; Sugita, Sunao; et al.
Abstract : Aims: The purpose of this study is to elucidate the clinical manifestations and the current treatment status of cytomegalovirus (CMV) endotheliitis via a large case series obtained from a national survey conducted in Japan. Methods: The Japan Corneal Endotheliitis Study Group proposed diagnostic criteria for CMV endotheliitis based on a viral examination by PCR of aqueous humour, in combination with clinical manifestations. A national survey was then retrospectively conducted among 1160 members of the Japan Cornea Society. The study reviewed the patient profiles, clinical manifestations, and treatment modalities of individuals who met the diagnostic criteria for CMV endotheliitis. Results: The study included 109 eyes of 106 patients. Mean patient age was 66.9±10.9 years (85 males (80.2%), 21 females (19.8%)). Patients were commonly diagnosed with anterior uveitis and ocular hypertension prior to confirmation of CMV endotheliitis. Coin-shaped lesions were observed in 70.6%, and linear keratic precipitates in 8.3% of the patients, respectively. 95% of cases were treated with anti-CMV drugs. Conclusions: CMV endotheliitis is most common in middle-aged and elderly men. CMV endotheliitis should be suspected when patients present with corneal endotheliitis involving coin-shaped lesions accompanied by anterior uveitis and ocular hypertension.